PBS - Frontline: Failure to Protect: The Taking of Logan Marr
The documentary tells the tragic story of Logan Marr, a 5-year-old girl, taken from a mother who never abused her and whose death while in foster care prompted the state of Maine in the U.S. to reexamine its child welfare policies.